CIPP MODEL EVALUATION ON THE IMPLEMENTATION OF THE MERDEKA CURRICULUM IN HINDU RELIGIOUS EDUCATION AND CHARACTER LEARNING AT SENIOR HIGH SCHOOL IN DENPASAR - Ida Ayu Gde Yadnyawati; Ni Made Indiani; Muliani, Ni Made (UHN IGB Sugriwa Denpasar, 2024)
Hindu religious education and character learning form people who have faith, are devoted to God Almighty, and have noble character in accordance with the goals of national education. This research is the most recent and was urgently carried out to assess and measure the success of the implementation of the Merdeka curriculum. So that, through the results of this research, improvements can be made to aspects that have not been optimally implemented and can become a basis for consideration when making policies related to the Merdeka curriculum. The aim of this research is to thoroughly analyze the evaluation of the CIPP model on the implementation of the Merdeka curriculum in Hindu religious education and character learning for X grade students at a senior high school in Denpasar City from the level of effectiveness. This type of research is survey research, and the approach used is an evaluative approach. For sampling, X-grade students use probability sampling techniques with simple random sampling; meanwhile, for sampling of school principals and deputy principals in the curriculum sector, non-probability sampling techniques with saturated sampling are used. The instrument used is a questionnaire with data analysis techniques using descriptive statistics. The results of this research are the level of effectiveness based on calculations using Glickman's theory, respectively, for students, educators, the deputy principal for curriculum, and the school principal at SMA N 1 Denpasar, namely, very effective, very effective, and very effective. Meanwhile, at SMA N 4 Denpasar, it is less effective, very effective, and very effective. At SMA N 7 Denpasar, less effective, very effective, and very effective.